The efficacy of red and blue light-emitting diode phototherapy combined with oral minocycline for acne conglobata: a retrospective cohort study - Hao, Yonghong; Zou, Xiaofang; Gao, Yixuan; Xing, Liyuan; Li, Chengxin (Frontiers in Medicine, 2026)
ObjectiveAcne conglobata (AC) is a severe inflammatory skin condition with limited therapeutic options that can provide rapid and sustained remission. This retrospective cohort study aimed to evaluate the clinical efficacy and safety of a combination therapy of twice-weekly red-blue light-emitting diode (LED) phototherapy with a shortened 4-week course of oral minocycline, compared to a conventional polypharmacy regimen for AC.MethodsWe analyzed clinical data from 28 outpatients diagnosed with AC. The study group (n = 15) received LED phototherapy (640 nm red and 460 nm blue light) and oral minocycline (100 mg/day for 4 weeks). The control group (n = 13) was treated with a heterogeneous conventional regimen, including oral isotretinoin and/or extended minocycline (8 weeks) plus topical agents. Efficacy outcomes, including Symptom Score Reduction Index (SSRI), Global Acne Grading System (GAGS), and Pruritus Visual Analog Scale (P-VAS), were assessed by blinded dermatologists at baseline and over 8 weeks. Safety and tolerability were also evaluated.ResultsBaseline characteristics were comparable between groups. The LED-minocycline combination resulted in significantly superior and more rapid clinical improvement. At week 8, 100% of patients in the study group achieved cure (SSRI ≥90%), versus 0% in the control group (p < 0.001). The mean SSRI in the study group was 92.1 ± 2.37% compared to 23.1 ± 4.35% in the control group (p < 0.001). The study group also showed significantly lower post-treatment GAGS scores (7.01 ± 2.01 vs. 9.03 ± 2.36, p = 0.022) and P-VAS scores (1.2 ± 0.6 vs. 4.8 ± 1.1, p < 0.001). Adverse events were mild and transient, with no significant difference in the incidence of skin irritation between groups (93.3% vs. 84.6%, p = 0.583).ConclusionCombining red-blue LED phototherapy with a 4-week course of minocycline is a rapid, highly effective, and safe therapeutic strategy for AC, outperforming conventional polypharmacy while halving the duration of systemic antibiotic exposure. Despite the inherent limitations of a retrospective design, these findings support the integration of LED therapy to optimize the management of severe acne.